A Novel route to synthesis of lead glycolate and perovskite lead titanate, lead zirconate, and lead zirconate titanate (PZT) via sol-gel process - Nuchnapa Tangboriboon (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2006